Single-incision laparoscopic appendectomy versus traditional three-hole laparoscopic appendectomy for acute appendicitis in children by senior pediatric surgeons: a multicenter study from China - Liu, Jie; Chen, Guoxian; Mao, Xiaowen; Jiang, Zhihui; Jiang, Nannan; Xia, Nan; Lin, Aiqin; Duan, Guangqi (Frontiers in Pediatrics, 2023)
Objective The aim of this study was to evaluate the clinical efficacy of single-incision laparoscopy appendectomy (SILA) and traditional three-hole laparoscopy appendectomy (THLA) for the treatment of acute appendicitis in children. Methods The clinical data of children (<14 years old) who underwent laparoscopic appendectomy at Yijishan Hospital of Wannan Medical College, Hubei Provincial Maternal Health Hospital and Qingdao Women and Children's Medical Center from January 2019 to June 2022 were retrospectively analyzed. According to the operation method, the patients were assigned to the SILA group or the THLA group. The clinical data, including the efficacy, and the surgical details, including the complications, of the two surgical methods were compared. The personal information of the children and the time of disease onset were recorded. Results In this study, the data of 588 patients, including 385 patients in the THLA group and 203 patients in the SILA group were collected. The baseline characteristics between the two groups of patients before surgery were comparable. There was no significant difference in the average operation time between the THLA group and the SILA group (56.31 ± 1.83 min vs. 57.48 ± 1.15 min, P > 0.05). There was also no significant difference in the average length of hospital stay between the THLA group and the SILA group (6.91 ± 0.24 days vs. 7.16 ± 0.36 days, P > 0.05). However, the FLACC scores of the SILA group (3.71 ± 0.78) were significantly lower than those of the THLA group (3.99 ± 0.56) on the second postoperative day, and the difference was significant (P < 0.05). The score of the questionnaire evaluating cosmetic appearance of the postoperative abdomen was significantly higher in the SILA group (15.81 ± 0.36) than in the THLA group (13.10 ± 0.24) (P < 0.05). There was no significant difference in the incidence of postoperative complications between the two groups (P > 0.05). Conclusion SILA is more advantageous in terms of postoperative FLACC scores and cosmetic appearance in children than THLA. There was no significant difference in the incidence of complications or other aspects between the two surgical methods.